Analysis of ISB watermarking model: block based methods vs embedding repetition methods - Zeki, Akram M.; Abdul Manaf, Azizah; S. Mahmood, Shayma'a (2011)
Digital watermarking technique based on intermediate significant bit (ISB) has been discussed by this study. This technique can survive against different types of attacks and at the same time keep the quality of the image. In this study, two improvement stages were applied, repeating the embedding and watermark embedding based on the average of pixels values. The results showed that the value of the Normalized Cross Correlation (NCC) was increased by increasing the embedding number of all the attacks. The results of the NCC for all the attacks became very close to 1 after nine repetitions. The results indicate that the method, based on the average of pixels values, is better for all the attacks as compared to based on repetition, except for rotation and scaling which improved extensively using the same method.